Genome-Wide Identification and Analysis of GATA Gene Family in Dendrobium officinale Under Methyl Jasmonate and Salt Stress - Zhangting Xu; Feixiong Zheng; Xiaoji Deng; Yiming Sun; Zhenming Yu; Xiaoxia Shen (Plants)
Dendrobium officinale, which was rich in bioactive compounds such as polysaccharides, alkaloids, amino acids, and flavonoids, had significant medicinal value and ability to resist stresses. Studies had demonstrated that GATA genes were one of the crucial regulators in controlling plant development and growth and stress response. Genome-wide identification and characterization of the 18 DoGATA genes were displayed. According to phylogenetic relationships, the DoGATA family genes were divided into 4 groups and the conserved motifs of DoGATA1–DoGATA18 within the same group were similar. All DoGATA genes were localized in the nucleus and randomly mapped on 10 chromosomes. The GATA genes in D. officinale experienced one pair of tandem duplication and 4 pairs of segment duplications to expand the family genes. Additionally, we found that the 2000 bp upstream promoter region of the DoGATA genes harbored 23 types of cis-acting elements that were categorized into plant growth and development, phytohormone responsiveness, and stress responsiveness. DoGATA1–DoGATA18 were diversely expressed across different tissues (root, leaf, stem, flower), exposed to salt stress, and following MeJA treatment. Co-expression analysis between DoGATA and enzyme-encoding genes involved in the biosynthesis of flavone showed that DoCHI (LOC110104562) and DoGTMT (LOC110098370) may be potential downstream targets of DoGATA16 to regulate flavonoid biosynthesis to adapt to salt stress. Furthermore, we confirmed that DoGATA16 may act as a key member to resist stress. The collective findings of this study shed light on the function of GATA genes and molecular breeding of D. officinale.